An Epidemiological Comparison of Elbow Injuries Among United States High School Baseball and Softball Players, 2005-2006 Through 2014-2015. (March 2018) - Pytiak, Andrew V.; Kraeutler, Matthew J.; Currie, Dustin W.; McCarty, Eric C.; Comstock, R. Dawn
Background: Pitching is a common mechanism of injury in baseball, with known risk factors for elbow injuries among adolescent pitchers. Hypothesis: Elbow injury rates and mechanisms will differ between high school baseball and softball players. Study Design: Descriptive epidemiology study. Level of Evidence: Level 3. Methods: Baseball- and softball-related injury data from the 2005-2006 through 2014-2015 academic years were collected from the High School Reporting Information Online (RIO) Internet-based data collection tool. Athlete-exposure (AE) and injury data were collected by certified athletic trainers. Rate ratios (RRs) were calculated comparing injury rates in the 2 populations. Injury proportion ratios (IPRs) comparing elbow injuries in pitchers and nonpitchers were calculated as the proportion of all elbow injuries in pitchers divided by the proportion of all elbow injuries in nonpitchers. Results: A total of 214 elbow injuries in male baseball players occurred over 2, 327, 774 AEs, for an overall elbow injury rate of 0.92 per 10, 000 AEs. A total of 75 elbow injuries were reported in female softball players over 1, 731, 644 AEs, for an overall rate of 0.43 per 10, 000 AEs. The rate of elbow injury was significantly higher for baseball than softball (RR, 2.12; 95% CI, 1.64-2.77). A significantly greater proportion of elbow injuries in baseball were pitching-related compared with those from softball, with 50.2% occurring while pitching in baseball versus 11.0% in softball (IPR, 4.58; 95% CI, 2.35-8.93). If all injuries occurring during pitching were removed from both sports, the difference in elbow injury rate for baseball and softball would no longer be significant (RR, 1.19; 95% CI, 0.88-1.62). Conclusion: The rate of elbow injuries is significantly higher in baseball than softball. This is attributable to differences in rates of pitching-related injuries between these 2 groups. Clinical Relevance: These results demonstrate that overhand pitching increases risk of elbow injury in high school athletes.